Предмет: Алгебра,
автор: гоз
Решить уравнение:
3(x+1)(x-1)=2(x-2)(x+2)+x^2+2x
Помогите пожалуйста!!!
Ответы
Автор ответа:
0
условие можешь не писать
Приложения:
Автор ответа:
0
(a-b)(a+b)=a²-b²
3(x+1)(x-1)=2(x-2)(x+2)+x²+2x
3(x²-1)=2(x²-4)+x²+2x
3x²-3=2x²-8+x²+2x
3x²-2x²-x²-2x= -8+3
-2x= -5
x= -5 / ( -2)
x=2.5
3(x+1)(x-1)=2(x-2)(x+2)+x²+2x
3(x²-1)=2(x²-4)+x²+2x
3x²-3=2x²-8+x²+2x
3x²-2x²-x²-2x= -8+3
-2x= -5
x= -5 / ( -2)
x=2.5
Приложения:
Похожие вопросы
Предмет: Биология,
автор: Аноним
Предмет: История,
автор: nastya310605
Предмет: Қазақ тiлi,
автор: saparovakalia
Предмет: Физика,
автор: Аноним
Предмет: Биология,
автор: 159951g